Exploring Genetic Variation and Trait Correlations in ‘Shiqian Taicha’ Tea Based on Comprehensive Analyses of Morphological and Biochemical Diversity - Kaiqin Lin; Anran Wang; Yuexin Li; Lulu Li; Jie Wei; Fuyu Zhou; Degang Zhao; Donghai Yan (Horticulturae)
This study explores the genetic variation and trait correlations within a collection of 52 ‘Shiqian Taicha’ tea germplasms originating from Shiqian County, Guizhou Province, China. The ‘Shiqian Taicha’ landraces exhibit substantial genetic diversity and are characterized by unique morphological and biochemical attributes. The Shannon-Weaver diversity index (H’) values for the morphological traits ranged from 0.37 to 2.06, with an average value of 1.02, which suggests a greater level of genetic diversity than those of other domestic tea germplasms. The biochemical analysis demonstrated considerable variation, with coefficients of variation (CVs) for biochemical components ranging from 3.73 to 54.05% (mean CV: 20.35%). In addition, 25 germplasms had epigallocatechin-3-gallate (EGCG) contents ≥ 10%. The correlation analysis revealed significant associations between morphological traits and biochemical components, with particularly positive correlations between the leaf texture and key biochemical components such as total catechins (TC) and EGCG (p < 0.01). The clustering analysis, which was based on morphological and biochemical profiles, further categorized the tea germplasms into distinct groups. Notably, SWD-G, SLD005, SWXD005, and SWD004 were identified as superior germplasms with comprehensive biochemical qualities and high EGCG contents. These unique resources have potential for the cultivation of specific tea varieties with regional characteristics.